Heterochronic changes during embryonic development of neotropical foam nesting frogs (genus Leptodactylus) - Grosso, Jimena Renee (2017)
At least five different reproductive modes were reported in the neotropical frog genus Leptodactylus, all of them involving the building of foam nests. We analyzed the early ontogeny of five species of the L. fuscus group building terrestrial chambers where eggs are deposited, and of two species of the L. latrans group constructing a floating nest over the surface of lentic waters. The ontogenetic period described herein includes the occurrence of exclusively embryonic structures and the initial stages of development of larval features. In a likely relation to ecological aspects of oviposition and developmental mode, embryos of these two groups differ in several features. Embryos of the L. fuscus group were mainly pigmentless, were large sized with an extensive yolk provision, showed a dorsal kyphosis and lacked adhesive glands. Conversely, embryos of the L. latrans group were darkly pigmented, lacked a dorsal curvature, were comparatively smaller and less yolked, and showed adhesive glands in a peculiar type D morphogenetic pattern. Embryos of the L. latrans group had long, profusely branched, highly ciliated external gills, which were arranged ventrally. The comparative analysis of developmental sequences revealed an early emergence of hind limbs in Leptodactylus species relative to a reference leiuperine trajectory, an earlier differentiation of external gills in the species of the L. fuscus group, and an overall earlier development of mouthparts in embryos of the L. latrans group. Further analyses in a phylogenetic context are needed to evaluate the ancestral reconstructions of the development sequence and detect evolutionary relevant heterochronies in the genus.